ANALISIS MULTIPLIER PENGELUARAN PEMERINTAH TERHADAP KONTRIBUSI EKONOMI DI NEGARA-NEGARA G20 BERDASARKAN TEORI KEYNES - Jalaluddin Iman Rahadianto; Ignatia Martha Hendrati; Wirya Wardaya (Universitas Nias Raya, 2026)
The government plays an important role in boosting GDP and maintaining economic stability in a country, especially in G20 member countries. Economic balance can be achieved when aggregate expenditure equals national income. Therefore, this study was conducted to examine the impact of government spending, open trade, and government debt on economic contribution in G20 countries. Economic contribution is the ratio of the real GDP of each G20 member country to the average real GDP of all G20 member countries. The research method used is quantitative analysis with Panel-Fix Effect Data through Keynes' theory as the grand theory. The results show that government spending plays a constructive role in increasing economic contribution, open trade has a negative impact on economic contribution, while government debt actually suppresses economic contribution. Thus, this study confirms that economic contribution in G20 countries is influenced by a combination of fiscal instruments, trade structure, and state financing policies in a multiplier effect. Balance in the policies issued by the government is the key to maintaining economic stability.